2019
DOI: 10.1111/jnc.14644
|View full text |Cite
|
Sign up to set email alerts
|

VGLUT3 gates psychomotor effects induced by amphetamine

Abstract: Several subtypes of modulatory neurons co‐express vesicular glutamate transporters (VGLUTs) in addition to their cognate vesicular transporters. These neurons are believed to establish new forms of neuronal communication. The atypical VGLUT3 is of particular interest since in the striatum this subtype is found in tonically active cholinergic interneurons (TANs) and in a subset of 5‐HT fibers. The striatum plays a major role in psychomotor effects induced by amphetamine. Whether and how VGLUT3‐operated glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…In rodents, a single administration of d-amphetamine induces a broad repertoire of motor behaviors ranging from increased locomotion (from 2 to 5 mg/kg) to repetitive/stereotyped motor sequences (above 5 mg/kg) (Crittenden et al, 2014;Mansouri-Guilani et al, 2019;Valjent et al, 2010;Yates et al, 2007). Our results indicate that the latter are correlated with an increased expression of pS32-cFos in neurons in the ventral horn of the spinal cord, a spinal region harboring neural circuits dedicated to execution and generation of rhythmic motor behaviors (Grillner and El Manira, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…In rodents, a single administration of d-amphetamine induces a broad repertoire of motor behaviors ranging from increased locomotion (from 2 to 5 mg/kg) to repetitive/stereotyped motor sequences (above 5 mg/kg) (Crittenden et al, 2014;Mansouri-Guilani et al, 2019;Valjent et al, 2010;Yates et al, 2007). Our results indicate that the latter are correlated with an increased expression of pS32-cFos in neurons in the ventral horn of the spinal cord, a spinal region harboring neural circuits dedicated to execution and generation of rhythmic motor behaviors (Grillner and El Manira, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…These non-serotonergic neurons have also been implicated in reward ( McDevitt et al, 2014 ) and have even been shown to mimic addictive phenotypes produced by VGLUT3 knockout. For example, the knockout of specifically cholinergic, but not serotonergic VGLUT3 neurons, is responsible for the aforementioned amphetamine-sensitisation ( Mansouri-Guilani et al, 2019 ). It is therefore important that future studies be performed which immunologically dissect these VGLUT3 projections, for example by additionally probing for acetylcholine axons.…”
Section: Discussionmentioning
confidence: 99%
“…Given its involvement in striatal circuitry, VGLUT3 signaling regulates the phenotypic behavior induced by drugs of abuse. Global loss of VGLUT3 blunted acute and chronic amphetamine-induced stereotypies, an effect coupled with marked reduction in ΔFosB expression levels in murine striatal tissues (Mansouri-Guilani et al, 2019). Furthermore, striatal VGLUT3 signaling regulates cocaine rewarding properties, albeit in a manner different from mGluR5.…”
Section: Drug Addictionmentioning
confidence: 94%